Influence of zinc on yield and quality profile of ginger (Zingiber officinale Rosc.) - C R Nileena, R Dinesh, S Hamza, N K Leela, V Srinivasan (Journal of Spices and Aromatic Crops, 2013)
Field experiments were conducted for three consecutive years (2008–09. 2009–10, 2010–11) in a Zn deficient soil to study the variation in quality and oil composition of ginger due to incorporation of Zn in the fertilizer schedule. The treatments consisted of recommended package of practice (POP) without zinc, POP + 5 kg Zn ha-1, POP + 10 kg Zn ha-1 as zinc sulphate. The results showed that application of Zn increased the fresh yield of ginger from 7.72 to 9.57 kg 3m-2 indicating an increase of 23%. Zinc application also increased the oil, oleoresin, β-sesquiphellandrene, farnesene, camphene and Z-citral contents of ginger oil. Contrarily, Zn application decreased zingiberene, α-pinene, α-curcumene and 1, 8 cineol contents of ginger oil. The quality components such as fiber content varied from 3.05% to 3.43%, oil content from 1.33% to 1.73%, oleoresin from 3.35% to 5.41%, zingiberene from 13.1% to 21.8%, α- pinene from 0.67% to 2.23%, β-sesquiphellandrene from 5.92% to 10.20%, farnesene from 5.58% to 11.1%, camphene from 3.06% to 5.36%, Z-citral from 3.73% to 6.54%, α-curcumene from 5.32% to 7.70%, 1,8 cineol from 2.70% to 5.29%, β-phellandrene from 1.87% to 4.18% and citral contents from 5.03% to 6.54%.